Dynamic Soil Structure Interaction Behaviour of Building Frames with Strip Foundation using SAP 2000 - Shwetha J. (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Conventional method of structural analysis adopted for practical design of most of structures, ignores the effect of soil compressibility medium. It causes an underestimation of forces in certain members leading to unsafe design. For a realistic estimation of design forces, it is necessary to carry out analysis considering soil structure interaction. Hence, the analysis, which considers the flexibility characteristics of soil, foundation and superstructure, is called as interaction analysis. The soil structure interaction can be ignored, probably if the structure is very flexible or differential settlements under the column are negligibly small. Only a limited number of studies have been made on soil-structure interaction effect for three-dimensional space frames and few of them, carried to observe maximum possible extent of the effect of excitation frequency on seismic response of building. Therefore, this study compares the behaviour of the soil-structure interaction between seismic three-dimensional building with combined footing supported by soil types and also rigid bases. Such a study helps in providing guidelines to determine more precisely how seismically vulnerable building frames resting on strip foundations are, also being valuable for seismic design.